A localist's critique of Hong Kong's political development: Political decay, legitimacy crisis and reverse democratization. Issue 1 (2nd January 2018) - Chi Loo, Jeff Hai
Abstract : Purpose: This paper intends to explore the localist perspectives concerning Hong Kong's political development. The persistent growth of localists in the polity of the Hong Kong Special Administrative Region (HKSAR) has not only challenged the current political order but also aroused Beijing's national security considerations. The oath-taking controversies of 2016 demonstrated the strife that now exists between Beijing and the localists in Hong Kong. The purpose of this paper is to analyze the localists' perceptions of the political decay, legitimacy crisis and reverse democratization in HKSAR to illuminate further their perceptions of Hong Kong's political development. Design/methodology/approach: This paper uses the theoretical discussion of the relations between political decay, legitimacy, the legitimacy crisis and reverse democratization as the key analytical framework to understand the localists' perspective concerning Hong Kong's political development. Based on an analysis of the localists' discourse, the implication for the HKSAR regime's legitimacy and for reverse democratization will be discussed. Findings: The emergence of the new localists leads to the belief that Hong Kong's political development is experiencing the reverse of democratization as the government cannot fully absorb the demands made by the general public. The reverse democratization is directly impacting the regime's legitimacy, but in the HKSAR's case, the new localists see the root of the problem as stemming from Beijing, that is that the Chinese Communist Party's legitimacy problem is due to its underdevelopment in the legal, political and cultural spheres. This underdevelopment has weakened the legitimacy of the HKSAR's administration, especially with regard to political reform, the legal interpretation of the Basic Law, and the influx of immigrants and tourists from the Mainland into the Hong Kong's society. The China factor, from the Localists' viewpoint, is at the root of the political decay and the legitimacy crisis in Hong Kong. More significantly, the localists regard the involvement of Beijing in Hong Kong's affairs as its way to disrupt the autonomous status of the HKSAR. As a result, public discontent has further intensified and created the legitimacy crisis for the HKSAR Government. Originality/value: This paper is the first academic paper to provide a critical analysis of Hong Kong's localists' views regarding Hong Kong's political development since becoming the HKSAR. In contrast with the existing literature about Hong Kong's democratization and political development, this paper introduces localists' views and advocates the idea of "reverse democratization" to explain their perceptions concerning Hong Kong's political development.